Evaluasi Beban Kerja Mental Metode SWAT dan Intensitas Pencahayaan Terhadap Kelelahan Operator PT XYZ Berdasarkan Waktu Reaksi - Mila Mutiara Labibah; Siswiyanti Siswiyanti; M Fajar Nurwildani (Jurnal Teknik Industri Terintegrasi (JUTIN), 2026)
This study analyzes the effect of mental workload and lighting intensity on operators' reaction time before and after lamp replacement, and examines differences in mental workload and reaction time resulting from the intervention. This applied quantitative study involved 32 production operators from five departments (casting, grinding, welding, assembly, and stamping), with mental workload measured using the ASWAT questionnaire adapted from SWAT (Luximon & Goonetilleke, 2001), lighting intensity measured with a lux meter referring to SNI 7062:2019, and reaction time measured using a reaction time meter. Data were analyzed using Pearson correlation, simple linear regression, the Shapiro-Wilk test, and the paired sample t-test. Results showed mental workload had a significant positive correlation with reaction time before the intervention (r=0.520; p=0.002) but weakened afterward (r=0.291; p=0.106). Lighting intensity had a significant negative correlation before the intervention (r=-0.377; p=0.034; contribution 14.2%) but was no longer significant afterward (p=0.697). Mental workload (1.84→1.72; p=0.000) and reaction time (247.29→206.56 ms; p=0.021) decreased significantly, indicating improved workplace ergonomics.